Small government, big problems: climate change adaptation policy in North American Great Lakes localities - Gelardi, Carrington, author; Schomburg, Madeline, advisor; Scott, Ryan, committee member; Mumme, Stephen, committee member; Denning, Scott, committee member (Colorado State University. Libraries, 2022)
The Great Lakes region is home to 30 million people, one of the world's largest economies, and the world's largest freshwater ecosystem. These characteristics make the region uniquely vulnerable to climate change. Local governments in the area are subject to the impacts of climate change whether they are prepared for them or not. To explore this issue, this paper seeks to answer the question, "What is the state of local climate change adaptation policy in the Great Lakes region?" Most literature that exists on local adaptation focuses on larger cities with populations over 50,000 people. This project fills that gap by looking at climate plans from all U.S. local governments that border the Great Lakes regardless of their size. To do this, climate change adaptation plans and policies were gathered from each county and sub-county municipality (such as cities, villages, towns, and townships) in the United States that border the Great Lakes. A text analysis was performed that compared the documents to regional climate science, as well as an inductive content analysis to pull out the major topics in each plan. Local governments in the Great Lakes region are in the beginning stages of adapting to climate change. 6% sent back relevant policies. Many of them were small governments with under 20,000. Findings suggest a lack the capacity to adequately adapt, especially within the smallest governments. The degree of assistance needed from larger institutions to supplement any insufficiencies is still unclear. The results of this project capture a snapshot of how local governments bordering the Great Lakes are (or are not) adapting to climate change. This can be used to foster intergovernmental learning on how sub-state governments in the region can adapt, while also providing insight into the boundaries of local action in the face of a global issue.
Keywords: climate change; Great Lakes; public policy; environmental policy; adaptation; local government